2018
DOI: 10.18632/oncotarget.24720
|View full text |Cite|
|
Sign up to set email alerts
|

2’-Hydroxyflavanone effectively targets RLIP76-mediated drug transport and regulates critical signaling networks in breast cancer

Abstract: Breast cancer (BC) is the most common cancer in women. Estrogen, epidermal growth factor receptor 2 (ERBB2, HER2), and oxidative stress represent critical mechanistic nodes associated with BC. RLIP76 is a major mercapturic acid pathway transporter whose expression is increased in BC. In the quest of a novel molecule with chemopreventive and chemotherapeutic potential, we evaluated the effects of 2'-Hydroxyflavanone (2HF) in BC. 2HF enhanced the inhibitory effects of RLIP76 depletion and also inhibited RLIP76-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…We found that compared to control, 2HF alone inhibited BC cell proliferation in vitro and reduced tumor growth and weight in vivo. In addition, 2HF suppressed in vitro and in vivo levels of RLIP76 proteins, aberrant expression of which has been reported in various cancer types . The striking finding was that RLIP76 could be a biologically relevant target of 2HF in BC cells as over‐expression of RLIP76 caused a sustained decrease in the efficacy of 2HF across all time points tested (GFP‐RLIP76 + 2HF as compared to 2HF, Figure B).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…We found that compared to control, 2HF alone inhibited BC cell proliferation in vitro and reduced tumor growth and weight in vivo. In addition, 2HF suppressed in vitro and in vivo levels of RLIP76 proteins, aberrant expression of which has been reported in various cancer types . The striking finding was that RLIP76 could be a biologically relevant target of 2HF in BC cells as over‐expression of RLIP76 caused a sustained decrease in the efficacy of 2HF across all time points tested (GFP‐RLIP76 + 2HF as compared to 2HF, Figure B).…”
Section: Discussionmentioning
confidence: 62%
“…The rationale for selecting RLIP76 as one of the targets of 2HF stems from the following observations. First, RLIP76 is a selectively over‐expressed in cancer cells . Second, blocking of RLIP76 with antibodies or depleting with antisense increases sensitivity to chemotherapy and results in significant tumor reduction in colon, prostate, and lung carcinomas and B16 melanomas in mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations